Coming of age in Mississippi : the classic autobiography of growing up poor and black in the rural south - Moody, Anne (New York A Dell book, 1976)
Amy Moody shares her experiences growing up in the rural South in the 1940s and 50s, and explains how she became involved in the civil rights movement. A deeply personal story but also a portrait of a turning point in our nation's destiny, this autobiography lets us see history in the making, through the eyes of one of the foot soldiers in the civil rights movement.
Keywords: Moody, Anne -- Biografías; Mujeres norteamericanas -- Situación social -- Siglo 20o